State Funding for Education Technology and School Infrastructure: Competing Demands and Limited Resources - Faith E. Crampton (Educational Considerations, 2004)
In spite of signs of an economic recovery at the national level, many states still face formidable fiscal problems. In addition, the national fiscal outlook is compromised by a growing federal deficit, slow growth in job creation, and lingering unemployment in many parts of the country.